Public assessments of the police and policing in Hong Kong - Adorjan, Michael (The Australian and New Zealand journal of criminology, 2017)
This paper presents the findings from a focus group research study on public assessments of the police and policing in Hong Kong. The main findings indicate that while people have generally positive views about police effectiveness in responding promptly to and fighting crime, they have decidedly mixed views regarding stop and search and public order policing. By drawing on the multi-dimensional framework of trust proposed by other policing scholars, we suggest that a useful way to conceptualize public assessments of the police and questions of satisfaction and trust of policing in Hong Kong is to distinguish between people's instrumental concerns about personal safety and crime and their affective concerns about the process of policing and the symbolic role of the police in maintaining a particular way of life. The paper concludes by reaffirming the value of sociologically informed, qualitative policing research that examines questions of police-citizen relationship and legitimacy within a broader socio-political context.